Bio-conjugated silver nano-materials and shape-directing role of cetyltrimethylammonium bromide (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Conventional UV-visible spectrophotometric and transmission electron microscopic technique were used to determine the morphology of silver nanoplates (AgNP) using Alstonia scholaris aqueous leaves extract for the first time. The visible spectra showed the presence of three well defined surface plasmon absorption (SRP) bands at 500, 550 and 675 nm which attributed to the anisotropic growth of Ag-nanoplates. Transmission electron microscopic (TEM) analysis of AgNP showed formation of truncated triangular, polyhedral with some irregular shapes nanoplates in the size range 7-20 nm. Cetyltrimethylammonium bromide (CTAB) has no significant effect on the shape of the spectra, position of SRP bands, size and the size distribution of AgNP. Effects of various [CTAB] were also discussed in the green extra-cellular synthesis of AgNP using Alstonia scholaris leaves extract.